Notary Staff Liability for Forgery of the Signature of the Deed of Power of Attorney to Sell - Cestri Enggardini Budiarti; Jadmiko Anom Husodo; S. Sulistyanta (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2025)
A notary staff member was found to have participated in the criminal act of forgery of signatures together with the notary public on 4 Deeds of Power of Attorney to Sell. As a result, the owner of the Certificate of Ownership suffered losses. The problem in the decision focuses on the judge's decision to sentence only the notary public to a prison sentence of 1 year and 6 months and has become legally binding while the notary staff member is free from all legal charges. In fact, both the notary public and his staff were involved in the criminal act of forgery of authentic deeds. The difference in responsibility between the notary public and his staff is something that needs to be studied in relation to the implementation of the law regarding the crime of forgery of authentic deeds because the notary staff has fulfilled the requirements to be involved in the crime of forgery of deeds as regulated in the Criminal Code. Therefore, the purpose of this article is to discuss the actions of the notary staff member which constitutes a violation of the law by participating in the crime of forgery of authentic deeds. This research was conducted using normative legal research conducted through a review of literature sources. The approach applied to discuss the problems in this research is through a case approach. The method of collecting materials was carried out through library research. Data was then obtained from primary and secondary legal materials. The obtained materials were then analyzed using a qualitative analysis approach.